Rates of Return and Cash Flow Profiles: An Extension - Gordon, Lawrence A.; Hamer, Michelle M. (The Accounting Review, 1988)
[The cash recovery rate (CRR) has recently received attention as a basis for obtaining a measure of the economic rate of profitability of a firm as measured by its internal rate of return (IRR). This paper extends prior work by developing a model of the CRR-IRR relation which incorporates a commonly noted concave cash flow pattern for the firm's projects. The model forms the basis for converting an estimate of the firm's CRR into an estimate of its IRR. Empirical evidence is provided that the IRR estimates that are based upon the concave cash flow pattern are strongly associated with the IRR estimates based on the simpler cash flow profiles assumed in earlier work.]